Female authorship of covid-19 research in manuscripts submitted to 11 biomedical journals: cross sectional study. (6th October 2021) - Gayet-Ageron, Angèle; Ben Messaoud, Khaoula; Richards, Mark; Schroter, Sara
Abstract: Objective: To describe prominent authorship positions held by women and the overall percentage of women co-authoring manuscripts submitted during the covid-19 pandemic compared with the previous two years. Design: Cross sectional study. Setting: Nine specialist and two large general medical journals. Population: Authors of research manuscripts submitted between 1 January 2018 and 31 May 2021. Main outcome measures: Primary outcome: first author's gender. Secondary outcomes: last and corresponding authors' gender; number (percentage) of women on authorship byline in "pre-pandemic" period (1 January 2018 to 31 December 2019) and in "covid-19" and "non-covid-19" manuscripts during pandemic. Results: A total of 63 259 manuscripts were included. The number of female first, last, and corresponding authors respectively were 1313 (37.1%), 996 (27.9%), and 1119 (31.1%) for covid-19 manuscripts (lowest values in Jan-May 2020: 230 (29.4%), 165 (21.1%), and 185 (22.9%)), compared with 8583 (44.9%), 6118 (31.2%), and 7273 (37.3%) for pandemic non-covid-19 manuscripts and 12 724 (46.0%), 8923 (31.4%), and 10 981 (38.9%) for pre-pandemic manuscripts. The adjusted odds ratio of having a female first author in covid-19 manuscripts was <1.00 in all groups (P<0.001) compared with pre-pandemic (lowest in Jan-May 2020: 0.55, 98.75% confidence interval 0.43 to 0.70). The adjusted odds ratio of having a woman as last or corresponding author was significantly lower for covid-19 manuscripts in all time periods (except for the two most recent periods for last author) compared with pre-pandemic (lowest values in Jan-May 2020: 0.74 (0.57 to 0.97) for last and 0.61 (0.49 to 0.77) for corresponding author). The odds ratios for pandemic non-covid-19 manuscripts were not significantly different compared with pre-pandemic manuscripts. The median percentage of female authors on the byline was lower for covid-19 manuscripts (28.6% in Jan-May 2020) compared with pre-pandemic (36.4%) and non-covid-19 pandemic manuscripts (33.3% in Jan-May 2020). Gender disparities in all prominent authorship positions and the proportion of women authors on the byline narrowed in the most recent period (Feb-May 2021) compared with the early pandemic period (Jan-May 2020) and were very similar to values observed for pre-pandemic manuscripts. Conclusions: Women have been underrepresented as co-authors and in prominent authorship positions in covid-19 research, and this gender disparity needs to be corrected by those involved in academic promotion and awarding of research grants. Women attained some prominent authorship positions equally or more frequently than before the pandemic on non-covid-19 related manuscripts submitted at some time points during the pandemic.